The awakening of Sunshine Girl - McKenzie, Paige; Sheinmel, Alyssa B.; Hagen, Nick (McKenzie, Paige. Haunting of Sunshine girl, 2016)
"Sunshine Griffith can communicate with ghosts. Even more amazing, she recently discovered--with the help of her would-be boyfriend, Nolan--that's she's a luiseach, one of an ancient race of creatures who have lived among humans for centuries, protecting them from dark spirits and helping them move on to the afterlife. Now, Sunshine's powers are awakening and she feels spirits everywhere--intense and sometimes overwhelming. Eager to get her supernatural abilities under control, Sunshine agrees to begin training with her mentor, her estranged father Aidan. He takes her to an abandoned compound deep in the Mexican jungle. But what she learns there about her powers, and her family history, turns out to be more terrifying than Sunshine could have imagined. Can anything--Aiden's experiments, her friendship with another luiseach named Lucio, even Nolan's research--prepare Sunshine to face the frightening woman who haunts her dreams, and to finally learn the truth about the rift that threatens the future of the luiseach and all of humankind?"--Jacket.